Pengaruh Interkoneksi Distributed Generation Dalam Sistem Tenaga Listrik Terhadap Profil Tegangan - Bawan, Elias K; Hadi, Sasongko Pramono; Sarjiya, Sarjiya (2011)
Nowadays, new developments in electrical power generation technologies enable the electrical power to be generated by relatively small-scale power plants closed to the consumption centers, i.e. directly connected to the distribution networks. This paper shows the result obtained in the analysis of the voltage profile impact of distributed generation on distribution system. The main objective has been to determine if DG wheter increments or decrements distribution voltage profile based on location of DG and size of injection. The studied of this work was conducted on Feeder Maleo that connected to PraFi branch of Manokwari Electricity distribution system and used PLTU Prafi II as distributed generation. Analysis was done with power system simulator (PSS) on Electrical engineering laboratorium of Gadjah Mada University and validated with software ETAP 6.